2019
DOI: 10.1371/journal.pmed.1002869
|View full text |Cite
|
Sign up to set email alerts
|

Assessing trends in the content of maternal and child care following a health system strengthening initiative in rural Madagascar: A longitudinal cohort study

Abstract: Background In order to reach the health-related Sustainable Development Goals (SDGs) by 2030, gains attained in access to primary healthcare must be matched by gains in the quality of services delivered. Despite the broad consensus around the need to address quality, studies on the impact of health system strengthening (HSS) have focused predominantly on measures of healthcare access. Here, we examine changes in the content of maternal and child care as a proxy for healthcare quality, to better ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…12 From 2014 to 2016, care-seeking for childhood illness increased by 51% in PIVOT-supported areas and fell slightly in the rest of the district; attendance at four or more ANC visits increased for all areas of the district. 13 Beginning with a foundation of agreement and an enabling environment (Domain I), the NOC have been established within a health system where the vision is understood, and roles and responsibilities are delineated across levels of care and between NGO and state actors. Second, the NOC have sought to equip each level of the system with appropriate operational standards (Domain II), including the critical infrastructure necessary for service delivery, and the creation of linkages across the continuum of care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 From 2014 to 2016, care-seeking for childhood illness increased by 51% in PIVOT-supported areas and fell slightly in the rest of the district; attendance at four or more ANC visits increased for all areas of the district. 13 Beginning with a foundation of agreement and an enabling environment (Domain I), the NOC have been established within a health system where the vision is understood, and roles and responsibilities are delineated across levels of care and between NGO and state actors. Second, the NOC have sought to equip each level of the system with appropriate operational standards (Domain II), including the critical infrastructure necessary for service delivery, and the creation of linkages across the continuum of care.…”
Section: Resultsmentioning
confidence: 99%
“…PIVOT support to clinical programs, with a focus on child health, maternal and reproductive care, and infectious diseases, have resulted in significant improvements in the coverage and quality of care at facilities. 12,13 Specifically, PIVOT has accompanied the MoPH in the improvement of clinical programs such as Integrated Management of Childhood Illness (IMCI) at community-and CSB-level, malnutrition and tuberculosis, particularly through clinical skills building for health-care workers of each cadre and improved readiness, as mentioned above.…”
Section: Domain Iii: Quality Efficiency and Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A range of HSS programmes were initiated in a third of the district, ensuring health system readiness, improving clinical programmes and supporting integrated information systems at all levels of care. The first 2 years showed improved quality and coverage of primary care services, 30 and declines in child mortality rates. 31 The scope of the programmes and geographical footprint are being progressively scaled, and the government of Madagascar has designated Ifanadiana among the districts for piloting the national UHC strategy.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…In 2014, the Madagascar's Ministry of Health (MoH) and the nongovernmental organization PIVOT partnered to strengthen the public health system in the rural district of Ifanadiana, with the aim of attaining UHC and set a model for the country. Despite rapid improvements observed in accessibility and health conditions [50,51], initial analyses suggested that health gains were concentrated in close proximity to health centers [51]. Here, we aimed to develop very precise, context-specific estimates of geographic accessibility to care in Ifanadiana district to help with the design and implementation of interventions that improve access for remote populations.…”
Section: Introductionmentioning
confidence: 99%